1997
DOI: 10.1038/bjc.1997.278
|View full text |Cite
|
Sign up to set email alerts
|

Expression of insulin-like growth factors (IGFs), their receptors and IGF binding protein-3 in normal, benign and malignant smooth muscle tissues

Abstract: Summary To assess the role of insulin-like growth factors (IGFs) in growth and transformation of normal (myometrium) and tumorous smooth muscle cell (SMC) tissues, in situ hybridization (ISH) analysis for insulin-like growth factor and 11 (IGF-I and IGF-Il) mRNAs was combined with detection of IGF peptides, their receptors and IGF binding protein-3 (IGFBP-3). mRNAs for both IGFs were detected in smooth muscle cells in normal, benign and malignant SMC tissues, together with the IGF peptides, both IGF receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 45 publications
0
26
0
1
Order By: Relevance
“…The mRNA expression level of IGF-I was reported higher in leiomyomas than in the myometrium (26,29,30), although insulin and its receptor are not highly expressed in leiomyoma tissue (31). The levels of IGF-I receptors in leiomyomas have also been reported to exceed those of the myometrium (32)(33)(34), which suggests that IGF-I and the IGF-IR signaling pathway may be of major significance in the growth of uterine leiomyomas. There are limited studies done on the role of the hematopoietic growth factors, M-CSF-R, Fit-3, SCF-R, and MSP-R on uterine leiomyoma growth and development, although these RTKs were highly expressed in the leiomyomas compared with myometrial tissues in our RTK array studies.…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA expression level of IGF-I was reported higher in leiomyomas than in the myometrium (26,29,30), although insulin and its receptor are not highly expressed in leiomyoma tissue (31). The levels of IGF-I receptors in leiomyomas have also been reported to exceed those of the myometrium (32)(33)(34), which suggests that IGF-I and the IGF-IR signaling pathway may be of major significance in the growth of uterine leiomyomas. There are limited studies done on the role of the hematopoietic growth factors, M-CSF-R, Fit-3, SCF-R, and MSP-R on uterine leiomyoma growth and development, although these RTKs were highly expressed in the leiomyomas compared with myometrial tissues in our RTK array studies.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that osteoclast differentiation in leiomyosarcomas occurs by a RANKL-dependent mechanism in which mononuclear phagocyte osteoclast precursors in the TAM population interact with RANKLexpressing SMA + leiomyosarcoma cells. Leiomyosarcoma cells are known to produce a number of factors that promote RANKL-induced osteoclast formation including vascular endothelial growth factor (VEGF), insulin-like growth factor (IGF), and interleukin-6 (IL-6) [27][28][29]. VEGF regulates the expression of RANK, the receptor for RANKL, and can substitute for M-CSF to induce osteoclast formation [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The IGF-II/mannose 6-phosphate receptor appears to be a bifunctional receptor serving as both a lysosomal enzyme-targeting system and a suppressor of the action of IGF-II by increasing its degradation (Nissley and Lopaczynski 1991;Oates et al 1998). The levels of IGF-I receptors in leiomyomas have been reported to exceed those of the myometrium in three studies (Chandrasekhar et al 1992;Tommola et al 1989; Van der Ven et al 1997), whereas Chandrasekhar et al found no difference in the levels of the IGF-II receptors. The levels of neither IGF-I nor IGF-II receptors seem to vary with the stage of the menstrual cycle (Giudice et al 1993).…”
Section: Growth Factors Identified In Fibroidsmentioning
confidence: 95%
“…Both IGFs can bind to the IGF-I receptor with similar affinity, whereas the IGF-II receptor preferentially binds IGF-II ( Van der Ven et al 1997). The IGF-I receptor mediates most of the biologic actions of both IGF-I and IGF-II (Cohick and Clemmons 1993), including the mitogenic, metabolic, and cellsurvival properties of IGFs through tyrosine kinase signaling activity.…”
Section: Growth Factors Identified In Fibroidsmentioning
confidence: 99%